Methods of developing scientific imagination among public and private kindergarten teachers (Journal of the College of Basic Education, 2026)
he current research aims to identify the methods of developing scientific imagination among public and private kindergarten teachers, and the differences in the methods of developing scientific imagination among teachers according to the variable of kindergarten type (public - private). The researcher used the descriptive approach. The sample consisted of (100) teachers from public and private kindergartens. A scale was prepared to identify these methods consisting of (10) methods. Using appropriate statistical methods, the research reached the following results: Kindergarten teachers employ methods of developing scientific imagination in different ways, from the most common method being science fiction stories to the least common method being a computer program. There are also statistically significant differences in the use of methods among kindergarten teachers (public and private).